Clinical, epidemiological, and diagnostic characteristics of esophageal carcinoma in a Pakistani population - Muhammad Sohaib Asghar (Annals of Saudi Medicine, 2021)
BACKGROUND: Esophageal cancer ranks eighth among the most prevalent cancers globally and is the sixth leading cause of mortality from malignancy worldwide; it is the 7th most prevalent malignancy in males and the 6th most prevalent malignancy in females. In Pakistan, the incidence is 4.1 per 100 000 with the province of Baluchistan having the greatest incidence. OBJECTIVE: Report trends and characteristics of esophageal cancer in Pakistan over the past 10 years. DESIGN: Cross-sectional, retrospective review of medical records. SETTING: Tertiary care hospital. PATIENTS AND METHODS: The study included all patients admitted with a diagnosis of esophageal carcinoma with a mass lesion or luminal narrowing. The records were for the period from January 2011 to September 2020. MAIN OUTCOME MEASURES: Gender, histopathological types/differentiation along with clinical/laboratory findings. SAMPLE SIZE: 1009 with a mean (standard deviation) age of 49.3 (14.2) and a median (interquartile range of 50 (22) years (443 males and 566 females with age of 51.0 [20] years and 47.9 [23.8] years, respectively). The male-to-female ratio was 1:1.2. RESULTS: Most patients (82.7%) had squamous cell carcinomas with a male-to-female ratio of 1:2; the remainder had adenocarcinomas with a male-to-female ratio of 4:1 (P<.001). Dysphagia, weight loss, and vomiting were the most prevalent symptoms. More adenocarcinoma masses were located distally compared with squamous cell carcinomas (P=.030), lesions were most likely to be ulcerated (P=.910). Luminal narrowing was slightly more frequent in squamous cell carcinoma (P=.215), thickening was more prominently circumferential in the adenocarcinomas. In squamous cell carcinoma, the most common variant was moderately differentiated while moderate to poorly differentiated variants were more common in adenocarcinoma. In the survival analysis, squamous cell carcinoma (P=.014 vs adenocarcinoma), particularly the well-differentiated type (P=.018 vs other variants), projected a better prognosis. CONCLUSION: Our study reports the most recent trends of esophageal carcinoma in this region. LIMITATIONS: Lack of metastatic workup, TNM staging, and mode of treatment, along with the overlapping pattern of histological variants. CONFLICT OF INTEREST: None.